THE ROLE AND PRACTICALITY OF DIGITAL TEACHING TECHNOLOGIES IN ORGANIZING DRAWING LESSONS (Academicia Globe: Inderscience Research, 2023)
The role and practicality of digital teaching technologies in organizing drawing lessons in this article, as well as the organization of modern teaching technologies in drawing lessons detailed requirements.